(untitled) (Economic and Political Thought, 2015)
The lack of reliable domestic financial instruments, including a stable currency, results in domestic entities’ desire, and sometimes a need, to possess monetary resources from other currency areas. The phenomenon is called dollarization although it may relate to any currency, including mainly global currencies. The need for dollarization also appears in connection with the necessity of possessing reserves by the banking system. Official reserves made of world currencies that are kept by developing countries are definitely higher than required as standard traditional precautionary measures. It results from the lack of the international financial system solutions that might guarantee stable conditions for the functioning of developing economies, which makes them maintain high monetary reserves. Thus, it seems that dollarization of developing countries should be treated as an important factor shaping demand for world money. The specific share of the countries that are world currencies issuers, including first of all the dollar, in raising demand for world money that lets them solve their domestic problems is an issue that requires further analysis. On the other hand, the sources of these problems should be looked for in persistent defectiveness of neoliberal policy of the contemporary capitalism.